Fibronectin leucine-rich transmembrane protein 2 drives monocyte differentiation into macrophages via the UNC5B-Akt/mTOR axis - Fang, Yaxiong; Ma, Kongyang; Huang, Yi-Min; Dang, Yuanye; Liu, Zhaoyu; Xu, Yiming; Zheng, Xi-Long; Yang, Xiangdong; Huo, Yongliang; Dai, Xiaoyan (Frontiers in Immunology, 2023)
Upon migrating into the tissues, hematopoietic stem cell (HSC)-derived monocytes differentiate into macrophages, playing a crucial role in determining innate immune responses towards external pathogens and internal stimuli. However, the regulatory mechanisms underlying monocyte-to-macrophage differentiation remain largely unexplored. Here we divulge a previously uncharacterized but essential role for an axon guidance molecule, fibronectin leucine-rich transmembrane protein 2 (FLRT2), in monocyte-to-macrophage maturation. FLRT2 is almost undetectable in human monocytic cell lines, human peripheral blood mononuclear cells (PBMCs), and mouse primary monocytes but significantly increases in fully differentiated macrophages. Myeloid-specific deletion of FLRT2 (Flrt2ΔMyel) contributes to decreased peritoneal monocyte-to-macrophage generation in mice in vivo, accompanied by impaired macrophage functions. Gain- and loss-of-function studies support the promoting effect of FLRT2 on THP-1 cell and human PBMC differentiation into macrophages. Mechanistically, FLRT2 directly interacts with Unc-5 netrin receptor B (UNC5B) via its extracellular domain (ECD) and activates Akt/mTOR signaling. In vivo administration of mTOR agonist MYH1485 reverses the impaired phenotypes observed in Flrt2ΔMyel mice. Together, these results identify FLRT2 as a novel pivotal endogenous regulator of monocyte differentiation into macrophages. Targeting the FLRT2/UNC5B-Akt/mTOR axis may provide potential therapeutic strategies directly relevant to human diseases associated with aberrant monocyte/macrophage differentiation.